2021
DOI: 10.1093/mnras/stab1030
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological magnetogenesis: the Biermann battery during the Epoch of reionization

Abstract: We investigate the effect of the Biermann battery during the Epoch of Reionization (EoR) using cosmological Adaptive Mesh Refinement simulations within the framework of the Sphinx project. We develop a novel numerical technique to solve for the Biermann battery term in the Constrained Transport method, preserving both the zero divergence of the magnetic field and the absence of Biermann battery for isothermal flows. The structure-preserving nature of our numerical method turns out to be very important to minim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 64 publications
0
12
0
Order By: Relevance
“…The most popular model to explain the origin of seed magnetic fields in the Universe is the Biermann battery process (Biermann 1950). Small velocity drifts between electrons and ions in presence of misaligned electron density and electron pressure gradients generate microscopic currents and fields during the Epoch of Reionization at the level of 10 −20 G (Kulsrud et al 1997;Gnedin 2000;Garaldi et al 2021;Attia et al 2021). This is very far from the observed 10 −6 G observed in galaxies today and even 10 −4 G in the past.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…The most popular model to explain the origin of seed magnetic fields in the Universe is the Biermann battery process (Biermann 1950). Small velocity drifts between electrons and ions in presence of misaligned electron density and electron pressure gradients generate microscopic currents and fields during the Epoch of Reionization at the level of 10 −20 G (Kulsrud et al 1997;Gnedin 2000;Garaldi et al 2021;Attia et al 2021). This is very far from the observed 10 −6 G observed in galaxies today and even 10 −4 G in the past.…”
Section: Introductionmentioning
confidence: 83%
“…Another caveat of our model is how we set up the initial magnetic field. We used a uniform field with a strength of 10 −20 G, mimicking The topology of the Biermann generated fields is far more complex (see Attia et al 2021, for a recent study of the process). In the context of the subgrid turbulent dynamo, the topology and coherence length of the initial field is particularly important.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In future work (e.g. Attia et al 2021), we will look to model these alternative scenarios to determine their impact on the history of reionization and the first galaxies. Our simulations are among the first to simulate the epoch of reionization with fully coupled radiationmagnetohydrodynamics and thus represent an exciting milestone for cosmological numerical simulations.…”
Section: Discussionmentioning
confidence: 99%
“…The Biermann battery will generate magnetic fields as long as there is a gradient in the electron density that is perpendicular to a temperature gradient, for example, in an ionisation front sweeping over a gas filament. Gnedin et al (2000) post-processed cosmological simulations and found that this mechanism can generate seed magnetic fields on the order of 10 −21 in the IGM (see also Attia et al 2021) and the simulations of Garaldi et al (2020) show that the Durrive battery generates magnetic fields slightly weaker than those produced by the Biermann battery.…”
mentioning
confidence: 97%